2007
DOI: 10.1523/jneurosci.2299-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Human Cortical Activity during Streaming without Spectral Cues Suggests a General Neural Substrate for Auditory Stream Segregation

Abstract: The brain continuously disentangles competing sounds, such as two people speaking, and assigns them to distinct streams. Neural mechanisms have been proposed for streaming based on gross spectral differences between sounds, but not for streaming based on other nonspectral features. Here, human listeners were presented with sequences of harmonic complex tones that had identical spectral envelopes, and unresolved spectral fine structure, but one of two fundamental frequencies ( f 0 ) and pitches. As the f 0 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 54 publications
10
69
0
Order By: Relevance
“…Later, Gutschalk, Oxenham, Micheyl, Wilson, and Melcher (2007) presented human subjects with ABBB sequences consisting of harmonic complex tones with varying fundamental frequencies but identical spectral envelopes. As the pitch separation between the alternating tones increased, the subjects were more likely to hear two streams.…”
Section: H Brain Mechanisms Underlying Streamingmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Gutschalk, Oxenham, Micheyl, Wilson, and Melcher (2007) presented human subjects with ABBB sequences consisting of harmonic complex tones with varying fundamental frequencies but identical spectral envelopes. As the pitch separation between the alternating tones increased, the subjects were more likely to hear two streams.…”
Section: H Brain Mechanisms Underlying Streamingmentioning
confidence: 99%
“…A number of studies exploring the neural correlates of streaming based on pitch have found either no difference in activation between the left and right hemispheres, or activation primarily in the right hemisphere (Cusack, 2005;Gutschalk et al, 2005Gutschalk et al, , 2007Snyder et al, 2006;Wilson et al, 2007). In contrast, Deike, Gaschler-Markefski, Brechmann, and Scheich (2004) and Deike, Scheich, and Brechmann (2010) found activation primarily in the left hemisphere when subjects were asked to segregate A from B tones continuously in sequences where the tones differed in timbre or in pitch.…”
Section: H Brain Mechanisms Underlying Streamingmentioning
confidence: 99%
“…jneurosci.org as supplemental material). Such continuity illusion-related reductions were presumably caused by forward suppression (Wehr and Zador, 2005) or adaptation (Ulanovsky et al, 2003(Ulanovsky et al, , 2004 because these mechanisms in AC have been implicated also in possibly related auditory phenomena (Bregman et al, 1999) such as the integration of simple (Micheyl et al, 2005) or complex (Gutschalk et al, 2007) sound streams. It is conceivable that, in the case of continuity illusions, the early portion of the interrupted sound partially suppresses the neural response to the middle portion, provided that this middle portion is masked (see Introduction).…”
Section: Suppression As a Common Mechanism For Continuity Illusionsmentioning
confidence: 99%
“…This enhancement also correlated with behavioral reports of stream segregation. Similarly, Gutschalk et al (2007) described an increase of the P1m component for the A tone with increasing separation in fundamental frequencies (f 0 ) between harmonic complex tones in repeating ABBB_ sequences where A and B denote tones with different f 0 . In the second experiment of the earlier MEG study, Gutschalk et al (2005) directly compared magnetic fields evoked by B tones of a certain perceptually ambiguous ABA_ sequence when the subjects perceived two separate streams and when the subjects perceived one integrated stream.…”
Section: Introductionmentioning
confidence: 99%
“…They found a larger N1m amplitude during the perceptual organization of two separate streams both when the subjects followed the A or B tones and a larger P1 amplitude when the subjects followed the B tones. Gutschalk et al (2005Gutschalk et al ( , 2007 and Snyder et al (2006) suggested that reduced forward suppression may be the neuronal mechanism underlying the enhanced long latency components/fields during the perception of two segregated streams. The dipoles of these components/fields were located in the nonprimary auditory cortex.…”
Section: Introductionmentioning
confidence: 99%